“Struggle Is Our Way”: Assessing the Egyptian Muslim Brotherhood’s Relationship with Violence Post-2013 - Erika Biagini; Lucia Ardovini (Religions, 2022)
This article focuses on the Egyptian Muslim Brotherhood’s relationship with violence after the 2013 military coup. Following the Brotherhood’s sudden ouster from government, scholars predicted that renewed repression would lead to the radicalization of wings of the movement, particularly speculating that the youth would resort to violence as a way to respond to the regime. Indeed, calls in favor of the use of violence were recorded and associated with the activities of the New Office in Egypt during 2015, and with radicalization within the country’s prisons. Yet, this phenomenon has remained limited with reference to both time and context. Relying on interviews with members in Egypt, Turkey and the UK (2013–2021), this article critically unpacks the Brotherhood’s relationship with violence in the aftermath of the coup, investigating how the majority of Brotherhood members who subscribed to the movement’s peaceful resistance navigated nonviolent and violent strategies advocated by competing movements’ factions, as they became exposed to state-led violence. It looks at how members, male and female, endured repression, what role violence had in their resistance, if any, and how they justified it. The conclusion reflects on the role that violence plays in the Brotherhood’s strategies to reunite and rebuild after 2013.